Pendampingan Mitigasi dan Simulasi dalam Menghadapi Bencana Gempa Bumi dan Tsunami di Negeri Lima, Kecamatan Leihitu, Kabupaten Maluku Tengah - Kesaulya, Hertine Megiestri; Aswad, Wa Ode Sitti Jurianti; Rasyid, Risal (Jurnal Pengabdian Arumbai, 2024)
Negeri Lima is one of the villages in Central Maluku Regency, Maluku Province. As a village located in a coastal area, Negeri Lima is threatened by various natural disasters such as earthquakes and tsunamis. An earthquake followed by a tsunami hit Negeri Lima in 1674, resulting in material and human losses, therefore mitigation efforts need to be made to minimize the impact of natural disasters in the form of increasing the preparedness of the Negeri Lima community in facing the disaster. Mitigation efforts carried out can be in the form of structural mitigation, or non-structural mitigation. Non-structural mitigation can be carried out through disaster risk reduction activities by increasing community preparedness in facing disasters. The form of activity to increase community preparedness for disasters is through providing simulations in facing disasters. Departing from this problem, the community service activity carried out by the PKM team, namely "Mitigation Assistance and Simulation in Facing Earthquake and Tsunami Disasters" which was carried out on Wednesday, June 14, 2023, which was attended by 70 people. This activity is expected to increase community preparedness in facing earthquake and tsunami disasters. In addition, through this activity, the capacity of the Negeri Lima community can be increased, so that the risk of earthquake and tsunami disasters can be reduced.